Unipolar resistive switching of ZnO-single-wire memristors - Huang, Yong (Springer, 2014)
Well unipolar resistive switching (RS) behaviors were observed from Ag/ZnO single-microwire/Ag memristors. The reset voltages were larger than the set voltages, and all of them were less than 1 V. The resistance ratios of high-resistance state (HRS) to low-resistance state (LRS) reached 10(3). The bistable RS behaviors were entirely reversible and steady within 100 cycles. It was found that the dominant conduction mechanisms in LRS and HRS were ohmic behavior and space-charge-limited current (SCLC), respectively.